Characterization of spatio-temporal evolution of grain production and identification of its heterogeneity drivers in Sichuan Province based on Geodetector and GWR models - Dang, Huae; Deng, Yuanjie; Hai, Yifeng; Chen, Hang; Wang, Wenjing (Frontiers in Sustainable Food Systems, 2025)
Food security has become one of the central issues drawing global attention. Currently, the global food security situation is becoming increasingly urgent, profoundly impacting both China’s economic development and social stability, while also bearing significant national strategic importance. This paper is based on county-level grain production data from Sichuan Province between 2000 and 2022. Firstly, it employs methods such as standard deviation ellipses, center of gravity shifts, and spatial autocorrelation analysis to explore the spatiotemporal evolution of grain production in Sichuan Province. Furthermore, the Geodetector and GWR models are applied to identify and quantify the key drivers affecting grain production in Sichuan Province, as well as their spatial heterogeneity. The study finds that: (1) grain production in Sichuan Province shows a fluctuating growth trend, with clear regional disparities in its spatial distribution; (2) The spatial distribution of grain production in Sichuan Province exhibits a positive correlation, with its spatial association gradually strengthening, while also displaying significant spatial differences and regional clustering; (3) In terms of detecting driving factors, actual cultivated land area of the year has a significant impact on grain production, with its influence becoming particularly prominent when interacting with other factors; (4) Regarding the spatial heterogeneity of driving factors, each driver shows distinct spatial differentiation characteristics. Cultivated land area, fertilizer usage, and rural electricity consumption all exert a significant positive effect on overall grain production, while other influencing factors generally have a negative impact. This study not only deepens the scientific understanding of the spatiotemporal evolution and driving mechanisms of grain production but also provides scientific evidence and policy recommendations for food security and sustainable agricultural development in Sichuan Province and similar regions.